STUDYING THE CONFECTIONERY MARKET: IMPACT OF THE PANDEMIC AND WAR - Bochko , O.Yu.; Balyk , U.O.; Karpiy О.P. (The actual problems of regional economy development, 2022)
The article presents findings of the research on the confectionery market. The goal of the article is to announce findings of the research on performance of the confectionery market under the impact of Covid-19 pandemic and the Russian invasion of Ukraine. While conducting the research, the authors used different general scientific and specialized methods of research. In particular, the inductive and deductive methods were used to study search requests by Google Trends. The method of economic analysis and comparison was applied for analyzing the confectionery market. The graphical method was used for visual presentation of the results of the confectionery market analysis. To make theoretical generalization and conclusions, the authors applied the abstract and logical method. The work supplies calculations on the market shares of confectionery enterprises in Ukraine in 2020. To study development of the confectionery industry, Google Trends was used to find out the dynamics of popularity of the key works, like “sweets”, “biscuits”, “marmalade”, “wafers”, “candies”. It is determined that dynamics of the requests on the confectionery market changes depending on the season: the number of search queries increases when it is getting colder outside and decreases when a warmer season comes. In geographical terms, the research identifies top three regions with the greatest number of requests on sweets, namely Volyn, Ternopil and Ivano-Frankivsk. The following two regions are Rivne and Lviv. The search request on “chocolate” is the most popular word among the other kinds of confectionery products. The least popular are “wafers” and “marmalade”. The work supplies analysis of the structure of confectionery industry in Ukraine and performance of the main actors at the market. According to the results, the most popular search among the Internet users of Lviv region is “chocolate” (35%), the next popular is “biscuits” (32%), the third position is taken by “sweets” (21%). The confectionery market of Ukraine is made by above 850 enterprises. Currently, the most popular are such producers as Roshen, АVK, Konti, Svitoch, Mondeliz.